Clinical Needs Discovery in Pediatric Urology: Utilizing the Biodesign Process - Luff, Marie K.; Zarrin, David A.; Zhou, Li; Sahoo, Astha; Desai, Sophia; Iyer, Neha; Starr, Savannah L.; Sturm, Renea M. (Frontiers in Urology, 2022)
Introduction: Biodesign innovation processes provide a needs-driven approach to medical innovation, empowering both medical trainees and health care providers to take action in addressing the shortcomings of health care encountered in daily clinical practice1. Our objective was to uncover the most pressing unmet clinical needs within a specific clinical setting, pediatric urology at UCLA. Methods: The biodesign process involves a sequential process of identifying, validating, and prioritizing unmet needs, followed by solution landscaping and prototyping for the most promising needs1. Opportunities for medical innovation were first identified through six weeks of clinical immersion, which involved both clinical observation and interview-based insight extraction. Interviews were conducted with 35 stakeholders, including patients, patient families, and health care staff by a medical student participant in Sling Health LA, a program which provides innovation training and incubation for ideas. Follow-up interviews with key stakeholders were performed to validate needs. Priority scores were then assigned to each validated need using a series of pre-determined and weighted criteria. Finally, genealogy maps were constructed and used to guide subsequent solution landscaping for the top three needs. Results: 33 unmet clinical needs were identified throughout the clinical immersion phase, 27 of which were validated. Following coarse needs prioritization, five needs emerged as top contenders. After fine needs prioritization, three top needs were selected. The first top need arising from this ethnographic study was that “parents and children need a faster (<3 months to resolution) treatment option for resolving nocturnal enuresis that also prevents incontinence during the treatment phase”. Other discovered top needs included “parents and physicians need an accurate method to monitor retractile testes at-home and in the outpatient setting to reduce unnecessary surgical referrals and procedures”, and “a hospital system need to reduce complications and readmissions associated with post-operative catheter obstruction after urologic procedures”. A preliminary solution concept was generated for the top clinical need, nocturnal enuresis treatment. Conclusion: Biodesign processes offer a standardized method for identifying pressing unmet clinical needs and informing solution development. The top three needs discovered within pediatric urology through this ethnographic investigation represent promising innovation targets for further solution prototyping and design.